Lekiskon dalam Upacara Pernikahan Adat Sunda Huap Lingkung dan Sawer Panganten di Kabupaten Pandeglang: Kajian Etnolinguistik - Karimah, Nurul; Rosidin, Odien; Solihat, Ilmi (Universitas Lampung, 2025)
This study discusses the lexicon in Sundanese traditional wedding ceremonies in Kabupaten Pandeglang. This research aims to describe the lexicon and cultural meaning in traditional Sundanese wedding ceremonies Huap Lingkung and Sawer Panganten in Kabupaten Pandeglang. This research is expected to be a source of knowledge related to the lexicon of Sundanese traditional marriage so that these customs can continue to be preserved. The research method is a qualitative method with an ethnolinguistic approach. Data was collected through participant observation and in-depth interviews. The source of data in this research is a transcription of the recording of the researcher’s interviews with informants related to the lexicon and cultural meaning of traditional Sundanese wedding ceremonies. Based on the results of participant observation and in-depth interviews, the findings in this research included 24 data. The results of the research were 23 data found which were broken down into 12 lexcion data in the Sundanese traditional wedding ceremony Huap Lingkung which consisted of (1) monomorphemic words totaling 4 data; (2) polymorphemic words totaling 1 data; (3) verbal phrases totaling 4 data; and (4) nominal phrases totaling 3 data and 11 lexicon data in the Sundanese traditional wedding ceremony Sawer Panganten which consisted of (1) monomorphemic words totaling 5 data; (2) polymorphemic words totaling 1 data; (3) verbal phrases totaling 1 data and (4) nominal phrases totaling 4 data.Keywords: ethnolinguistic. lexicon, cultural meaning, Sundanese society